Classroom Interaction and Communication Strategies in English Learning: A Case Study at an Indonesian Elementary School (Conference on English Language Teaching, 2024)
In response to the needs of English language teaching in elementary schools, the case study explores the implementation of classroom interaction and communication strategies in English learning. This study aims to determine the learning strategies, communication process and the use of communication media applied in learning English in elementary schools. The data for this study involved English language teachers from an elementary school in Central Java, Indonesia. The study used qualitative methods by interviewing teachers to understand their views and experiences in managing classroom interactions and implementing communication strategies. The results from these interviews provided in-depth insight into teachers' practices for English language instruction at the primary level. The findings revealed that primary school students were more enthusiastic in learning. However, some obstacles were noted, including a shortage of projectors, the use of laptops, and the school's limited network. The implication of the research is that it provides valuable insights for curriculum development, teacher training and English language learning strategies at primary level, both in Indonesia and globally